Patellar ligament‐bone autograft for reconstruction of a distal patellar ligament defect in a dog. (6th March 2013) - Farrell, M.; Fitzpatrick, N.
<x xml:space="preserve">Abstract</x> A 3 · 5‐year‐old whippet was presented 4 weeks after sustaining a traumatic injury to the right stifle joint. A penetrating injury had resulted in patellar ligament (PL) rupture. Magnetic resonance imaging revealed a normal appearing proximal half of the PL and absence of normal fibres within the distal half of the ligament. Surgical repair involved reconstruction of the defect using an autogenous graft harvested from the medial third of the ipsilateral PL. This repair was augmented with a pedicle hamstring graft. A transarticular external skeletal fixator was used to protect the repair for 4 weeks. Seven months after surgery, the dog was able to exercise normally without lameness. To the author's knowledge, this is the first veterinary report of PL grafting of a PL defect, and the first report of surgical augmentation using a hamstring graft.